(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Self-esteem is a common problem in many countries, especially those affected by the pandemic. It is characterized by a lack of confidence and can make it difficult for students to concentrate and take risks. This study looks at the causes of low self-esteem and its effects on students. Education is an important aspect of human resource development. Poor academic performance has a negative impact on both the child’s self-esteem and the parents. Table 2 showed that the gender of the respondents was female, with 82% being female and 18% being male. Table 6 presented the mean of 2.57 as interpreted as a Great extent in Socializing, 2.55 as interpreted as Motivation, and 2.25 as interpreted as a Low extent. The overall weighted mean is 2.46. This study found that the majority of respondents were between the ages of 16 and 18 years old, with 82% female. It also found that 2.57 percent of students feel that Socialization has an impact on their academic performance. The researchers concluded that the outcome of the study is solely based on the facts and that the related Challenges of having low self-esteem in their academic performance are outweighed by having a 2.94. The researchers recommend this study to any student who is interested in dealing with this type of problem and is looking for a solution.